Developments in international exchange and payments systems: June 1992 - Flickenschild, Hans M... et al. (IMF WashingtonUS, 1992)
Covers developments during 1989 and 1990 with particular emphasis on developments in exchange systems; restrictive measures; bilateral payments arrangements and Council for Mutual Economic Assistance (CMEA) reform.